Modern Trends in Semiotic Research in the Media Field (2013-2022): A Second-Level Analytical Study - Hameed, Mohammed Mahmood (ALBAHITH ALALAMI, 2024)
To meet the scientific necessity, we conducted a study on the current situation of qualitative studies in the field of media applications, aiming to provide a comprehensive overview of academic output in this field, as well as to analyze the theoretical and methodological strengths and weaknesses. Therefore, this research paper addressed the modern trends in media research, focusing on the use of the semiotic approach in both Arab and Western schools. To achieve this, we analyzed 151 studies, distributed between Arab and foreign studies, from 2013 to 2022. The study concluded that there is a difference in the application of analysis approaches between Arab and foreign schools in the field of media, and that most Arab school researches are limited to the use of a few approaches without focusing on developments in the application of the semiotic method. Conversely, Western schools attempted to benefit from the application of this method, expanding the areas of analysis. Based on this, we can conclude that there is a future need to develop qualitative studies in the field of media, especially in the Arab school, by expanding the range of approaches used and focusing on developments in the application of the semiotic method.